2007
DOI: 10.1515/sg-2007-0015
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Superior Clones by Stability Analysis of Growth Performance in Populus davidiana Dode at Age 12

Abstract: Stability parameters and clone x site interactions for 12-year volume were investigated in seven Populus davidiana (Korean aspen) clonal trials in South Korea. Either 24 or 38 clones were tested in each of the seven sites. All sources of variables such as clone, site, and clone x site interaction were statistically significant (p < 0.01) in the analysis of variance. The average volume of 3,199 trees was 0.043 m 3 . The different types of stability were shown from selected clones against the test means for volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…The results were in agreement with Prakash (2006) for grain yield in Cicer aretinum. The present investigation supports the conclusion made by Koo et al (2007), and the adaptability should not only be the criterion for selecting superior genotypes, but also include ample consideration for growth performance and regression coefficient.…”
Section: Discussionsupporting
confidence: 89%
“…The results were in agreement with Prakash (2006) for grain yield in Cicer aretinum. The present investigation supports the conclusion made by Koo et al (2007), and the adaptability should not only be the criterion for selecting superior genotypes, but also include ample consideration for growth performance and regression coefficient.…”
Section: Discussionsupporting
confidence: 89%
“…For example, YU and PULKKINEN (2003) reported significant clone x site interaction for early growth of 24 hybrid aspen (Populus tremula x Populus tremuloides) clones in Finland. Similarly, significant GxE was detected for volume in Populus davidiana clones in Korea, but stable genotypes were identified which behaved in a predictable manner across sites (KOO et al, 2007). BALTUNIS et al (2008) reported evidence of GxE for height in 3year old clones of Pinus taeda tested in the southeastern United States which they hypothesized it was due to clones changing ranks on high-versus low-fertility sites, but little evidence of GxE for stable carbon isotope discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between genotype and environment (GxE) has been largely studied in plant breeding as a mean of producing new cultivars with stable and superior phenotypes [ 14 ]. GxE of individual traits have been assessed in numerous experiments with annual crops such as wheat [ 15 ], rice [ 16 ], oat [ 17 ] and soybean [ 18 ]; fibres such as cotton [ 19 ]; forest trees: poplar [ 20 ], pine [ 21 ], spruce [ 22 ]. Comparatively, fewer studies have been performed on fruit trees, including apple [ 23 , 15 ], wild cherry [ 24 ], and blueberry [ 25 ].…”
Section: Introductionmentioning
confidence: 99%